Long-term data storage media - Petrov, V. V.; Kryuchyn, A. A.; Belyak, E. V.; Shykhovets, O. V. (Інститут проблем реєстрації інформації НАН України, 2018)
The results of the analysis of media development technologies for long-term data storage are presented. It is shown that the use of hard disk drive and solid-state non-volatile media only partially solve the problem of long-term information storage. Particular attention is paid to modern technologies for storing data on optical media. It is shown that the latest developments of optical media are aimed at a significant increase of optical media capacity by means of the nanostructured recording materials use. It was shown that maintaining of the big data security and integrity includes request stability of the readout signal contrast and data errors rates for long and fixed period of time. Therefore capacity of single disk for long data memory should be high enough to store the whole data to avoid the variation of the baseline over many disks. It was proposed to develop optical storage based on a nanoplasmonic hybrid glass matrix. The nanoplasmonic hybrid glass composite has to be formed by a sol-gel process to incorporate gold nanorods into hybrid glass composite. Incorporation of the inorganic phase increases the local Young’s modulus of the host matrix around nanorods which helps to improve the lifespan of the shape of nanorods by removing the unwanted shape degradation susceptible to the environmental thermal perturbation and increase lifespan of the data storage. Proposed method could be compared with the spin coating method, paving a way to the low-cost large-scale mass production of the optical disks.